Pengaruh Regulasi Keuangan Islam terhadap Pertumbuhan Bank Syariah - Pane, Putri Marito; Bangun, Belliyani Br; Rahmadani, Fitri; Hasyim (Ikatan Da'i Indonesia, 2024)
This study explores the influence of Islamic financial regulations on the growth of Islamic banks, with a specific focus on qualitative methods and a literature review of previous articles. This approach provides profound insights into the development of Islamic banks in the context of Islamic financial regulations. The research identifies the need for financial regulations aligned with Sharia principles to ensure sustainable growth of Islamic banks, detailing the background of the importance of Islamic financial regulations in supporting the growth of Sharia-based financial institutions. The research methodology involves qualitative analysis of relevant literature, offering a comprehensive understanding of the impact of these regulations. The findings reveal that Islamic financial regulations play a significant role in strengthening and promoting the growth of Islamic banks. The conclusion emphasizes the importance of implementing and refining Islamic financial regulations as a key factor in enhancing the health and sustainable growth of Sharia-based financial institutions.